The Influence of Leadership Style and Compensation on Teacher Work Loyalty at Northern Green School - Robin; Andriaskiton, Mario; Buulolo, Asminta (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2023)
SD Northern Green School in Medan City is an alternative primary school in the city. The location of this school is at JL. Old Babura District No. 13. Medan Baru City of Medan Prov. North Sumatra, based on more detailed information. This study aims to determine the effect of leadership style and compensation on the work loyalty of teachers at Northen Green School Medan. The research method will involve the use of a questionnaire that is assessed using a Likert scale which provides choices of strongly agree, agree, disagree, neutral, agree, and strongly agree. Data analysis methods used include multiple linear regression analysis, coefficient of determination test, partial test, and simultaneous. The results of the study show that leadership style and compensation both simultaneously and partially affect employee loyalty.